Peran Purchasing Departemen Dalam Pengadaan Barang Pada PT. Jawa Metalindo Prima Industri: Laporan Kegiatan Kuliah Kerja Lapangan - Edwin Hidayat; I Gede Wiyasa; Harsono Teguh (Universitas 45 Surabaya, 2024)
PT. Jawa Metalindo Prima Industri was founded in 1985 by Mr. Suryanto Wibowo. Initially, the company focused on the production of small metal components and spare parts for the automotive industry. With strong determination and a vision to become a major player in the industry, PT. Jawa Metalindo Prima Industri started its journey with limited but quality production facilities. In the first few years, the company experienced steady growth. With increasing demand for metal products, PT. Jawa Metalindo Prima Industri is developing production capacity and improving the quality of its products. This is supported by investment in technology and modern production machines which enable the company to meet higher quality standards and increase production efficiency. In 1995, PT. Jawa Metalindo Prima Industri is diversifying its business by expanding its product range. The company began producing metal components for the electronics and household appliance industries. This step helps the company to diversify sources of income and reduce dependence on one particular market segment. At the beginning of the 21st century, PT. Jawa Metalindo Prima Industri is carrying out significant expansion. The company acquires several small companies in the same industry to expand its market share and gain competitive advantage. Apart from that, PT. Jawa Metalindo Prima Industri has also invested in improving production facilities, research and product development, as well as developing a qualified workforce. In recent years, PT. Jawa Metalindo Prima Industri continues to show positive growth. The company has succeeded in expanding its distribution network to export markets, so that its products can be sold to various countries throughout the world